Editorial: University and Entrepreneurship - Wit Pasierbek; Krzysztof Wach (Jesuit University Ignatianum in Krakow, 2016)
The theme of entrepreneurship education is present and discussed in our journal for the fourth time and enjoys a unique popularity among our authors and readers...